Broad framework for environmental project management - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. Today, organisations want to embed sustainable, environmental thinking into the way they reason, behave, and work.They want to avoid superficial “green-wash”.They want to make a difference.They also want an environmental reputation, but one that comes from their values, behaviours, and culture, rather than simple claims of corporate environmental responsibility (CER).They want to be able to demonstrate their environmental credentials, which can make a significant impact on how customers perceive the organisation and how markets and investors value the organisation.It is important to the people who work there as well.